Simultaneous Determination of 2-Nitrophenol and 4-Nitrophenol in Pharmaceutical Industrial Wastewater by Electromembrane Extraction Coupled with HPLC-UV Analysis - Saeid Yaripour; Ali Mohammadi; Somayeh Mousavi; Isa Esfanjani; Naghmeh Arabzadeh; Shahla Mozaffari (Tabriz University of Medical Sciences, 2019)
Background: In the present study, an electromembrane extraction (EME) followed by a simple high performance liquid chromatography with ultraviolet detection (HPLC-UV) was developed and validated for simultaneous determination of 2-nitrophenol (2-NP) and 4-nitrophenol (4-NP) in pharmaceutical industrial wastewater sample. Main parameters of electromembrane extraction were evaluated and optimized. Methods: 1-octanol was immobilized in the pores of a polypropylene hollow fiber as supported liquid membrane. As a driving force, a 100 volt electrical voltage was applied to transfer the analytes from the sample solution (pH, 7.5) through the supported liquid membrane into an acceptor solution (pH, 12). Results: The best enrichment factors were obtained 36 and 72 for 2-NP and 4-NP, respectively after 15 minutes of extraction. The effect of carbon nanotube, as a solid nano-sorbent on EME efficiency, was also evaluated. The proposed method provided the linearity in the range of 10-1000 ng/mL for 2-NP (R2> 0.9997) and 4-NP (R2> 0.9999) with repeatability range (% RSD) between 2.6-10.3 % (n = 3). The limit of detection was 3 ng/mL and the limit of quantitation was 10 ng/mL. Conclusion: Finally, the method was applied for the determination of 2-NP and 4-NP in industrial wastewater samples with relative recoveries in the range between 67-76 %. EME improved the sensitivity of HPLC-UV for the determination of trace concentrations of these analytes.